ANALISIS PENGARUH ETIKA KERJA ISLAM DAN KESESUAIAN KOMPENSASI TERHADAP KECURANGAN AKUNTANSI - M Karim; Syafrul Antoni (Accounting Department, Politeknik Negeri Bandung, 2024)
Abstract: This research aims to examine the influence of work ethics Islam And suitability compensation To fraud accountancy in the city river full. The sample in this study was 71 employee respondents part finance on office head village in City Sungai Penuh. Study This the result collected through questionnaire Which processed And analyzed use analysis regression multiple. Method Which Which used in determination sample in study This is technique Simple Random Sampling. Test The quality of the data in this research is the Pearson Correlation validity test and the test reliability using Cronbach's Alpha. To test hypotheses in research This, using the coefficient of determination test which has been adapted to the F test, test t. The results of the significance value of this research indicate that ethics Work Islam have a significant effect on fraud accounting in the river city is full with a significance value of 0.0 22 , and suitability compensation No have an influence on fraud accounting in the city of Full River with a significance value of 0.558 . And when testing is carried out together, all variable No influential in a way significance with mark as big as 0.68 0 . Keywords: ethics Work Islam , Compensation Suitability, fraud